A dual signal amplification nanosensor based on SERS technology for detection of tumor-related DNA. Issue 11 (10th December 2018) - Lin, Duo; Gong, Tianxun; Qiu, Sufang; Wu, Qiong; Tseng, Ching-Yu; Kong, Kien Voon; Chen, Guannan; Chen, Rong
Abstract : A dual signal amplification array based on SERS is developed by photo-triggered release of probes for reliable and sensitive DNA detection. Abstract : A dual signal amplification method based on surface-enhanced Raman scattering (SERS) is developed by photo-triggered release of SERS probes from mesoporous silica-coated Au nanorods (SiO2 @Au) and the use of a specially-designed SERS substrate with an internal reference. Two metal carbonyl (metal-CO) labels ( Os-S CO and Re-S CO) are proposed here as novel interference-free labels. Results demonstrate that tumor-related DNA can be quantitatively detected by this reliable and ultra-sensitive SERS platform.